Microbial community transcriptomes reveal microbes and metabolic pathways associated with dissolved organic matter turnover in the sea - McCarren, Jay (National Academy of Sciences, 2010)
Marine dissolved organic matter (DOM) contains as much carbon as the Earth's atmosphere, and represents a critical component of the global carbon cycle. To better define microbial processes and activities associated with marine DOM cycling, we analyzed genomic and transcriptional responses of microbial communities to high-molecular-weight DOM (HMWDOM) addition. The cell density in the unamended control remained constant, with very few transcript categories exhibiting significant differences over time. In contrast, the DOM-amended microcosm doubled in cell numbers over 27 h, and a variety of HMWDOM-stimulated transcripts from different taxa were observed at all time points measured relative to the control. Transcripts significantly enriched in the HMWDOM treatment included those associated with two-component sensor systems, phosphate and nitrogen assimilation, chemotaxis, and motility. Transcripts from Idiomarina and Alteromonas spp., the most highly represented taxa at the early time points, included those encoding TonB-associated transporters, nitrogen assimilation genes, fatty acid catabolism genes, and TCA cycle enzymes. At the final time point, Methylophaga rRNA and non-rRNA transcripts dominated the HMWDOM-amended microcosm, and included gene transcripts associated with both assimilatory and dissimilatory single-carbon compound utilization. The data indicated specific resource partitioning of DOM by different bacterial species, which results in a temporal succession of taxa, metabolic pathways, and chemical transformations associated with HMWDOM turnover. These findings suggest that coordinated, cooperative activities of a variety of bacterial “specialists” may be critical in the cycling of marine DOM, emphasizing the importance of microbial community dynamics in the global carbon cycle.